Development of ventricular fibrillation after implantation of a biventricular implantable cardioverter defibrillator: what is the mechanism?. Issue 7 (2nd June 2017) - Chemello, Diego; Pivatto Júnior, Fernando; Pimentel, Maurício; Zimerman, Leandro
Key Clinical Message: Syncopal spells in heart failure patient with cardiovascular implantable electronic devices (CIED) require multiple assessments. T‐wave oversensing is a well‐described phenomenon that remains significant in modern implantable cardioverter defibrillators (ICD) systems. It can lead to inappropriate therapies and loss of biventricular pacing in those with cardiac resynchronization devices. Strategies to overcome this problem are important. Abstract : Syncopal spells in heart failure patient with CIED require multiple assessments. T‐wave oversensing is a well‐described phenomenon that remains significant in modern ICD systems. It can lead to inappropriate therapies and loss of biventricular pacing in those with cardiac resynchronization devices. Strategies to overcome this problem are important.